A pastille combining myrrh tincture, peppermint oil and menthol to treat the upper airway - Öktemer, Tuğba; İpçi, Kağan; Bayar Muluk, Nuray; Cingi, Cemal (ENT Updates, 2015)
Myrrh and borax (combined in a tincture) can be used as a mouthwash. Myrrh gum is used to treat indigestion, ulcers, colds, coughs, asthma, lung congestion, arthritis pain, and cancer. Myrrh has been shown to exert analgesic effects on mice in which pain was induced. Myrrh is used as an astringent, antiseptic (to treat inflammed lesions of the throat and mouth), and antispasmodic to treat cancer and infectious disease. In this paper, we review the literature on myrrh tinctures, peppermint oil, and menthol.